"16+1 Cooperation" as a Long Lasting or Ad-hoc Project? Perspectives from Different Angles of Central and Eastern Europe". (1st January 2020) - Czerep, Jędrzej
Central and Eastern Europe's perception of the "Belt and Road" and its "16+1" partnership, is defined by specific characteristics of the region: it's pivotal location, historical experience of domination by stronger powers, and being one of the last regions which is not familiar with China's role of economic superpower. These factors contribute to cautious reception of the new initiative and to raising questions about its longlasting dimension. In different parts of the Central and Eastern Europe opinions among policy-makers, analysts, economists and public opinions vary on assessing seriousness of the project, its political and economic relevance. The article provides an overview of the major points of concern among the countries – participants to the "16+1 Cooperation".